Original Études for the Developing Conductor - Caldwell, Jonathan; Shapiro, Derek (Open textbook library., 2023)
Original Études for the Developing Conductor is a collection of supplemental études designed to enhance contemporary conducting pedagogy by amplifying the voices of composers from historically excluded groups. Each étude was commissioned from and composed by a living composer, the majority of whom are woman-identifying composers and/or composers of color. Each étude also addresses multiple specific pedagogical goals common to all conducting classrooms. Conducting textbooks commonly include musical examples to expose student conductors to various musical challenges and situations. However, due to the relative ease of using only music from the public domain, most examples found in commercially published books are excerpts of larger works composed by deceased cisgender white men of European descent. Often, this music bears little relation to a significant portion of the music contemporary students engage with and perform. These excerpts also tend to be quite short (i.e., less than a minute) and do not create cohesive, self-contained musical arcs. Instructors adopting or reviewing this text are encouraged to record their use on this form: https://bit.ly/original-etudes-interest. This helps the book's sponsors to understand this open textbook's impact. This project was made possible in part by financial support from the University Libraries at Virginia Tech Collaborative Research Grant, University of North Carolina at Greensboro University Libraries’ Textbook Affordability Program (TAP) Grants, and additional funding, technical, and publishing support from the Open Education Initiative of the University Libraries at Virginia Tech.